Are Sharia-Labeled Hotels Truly Sharia? Challenges In Implementing DSN-MUI Fatwa No. 108/DSN-MUI/X/2016: A Case Study from Pacitan, Indonesia - Dina, Arima Nur Rahma; Munfaridah, Imroatul (Invest Journal of Sharia & Economic Law, 2024)
The implementation of Sharia principles in the hospitality industry is crucial to meet the growing demand for halal tourism. This study examines the extent to which a Sharia-labelled hotel in Pacitan, Indonesia, applies the guidelines outlined in the DSN-MUI Fatwa No. 108/DSN-MUI/X/2016, focusing on the product, service, and management aspects. Through a qualitative field research approach involving in-depth interviews, participatory observation, and documentation analysis, the study reveals significant gaps between the hotel's Sharia-compliant branding and its actual practices. Notable deficiencies were found in the provision of prayer facilities, cleanliness standards, halal certifications for food and beverages, and adherence to Islamic financial principles. The absence of standard operating procedures to regulate guest behavior and ensure staff compliance with Sharia dress codes further highlights the challenges in aligning operations with Islamic guidelines. These findings underscore the need for a multifaceted approach to address discrepancies, including prioritizing the establishment of essential facilities, comprehensive staff training, and the development of clear operational procedures. At the policy level, this study emphasizes the importance of government support through financial incentives, capacity-building programs, and stricter enforcement mechanisms to ensure consistency and transparency in the use of Sharia-compliant labels. By bridging the gap between branding and practice, Sharia-compliant hotels can enhance their credibility and contribute to sustainable growth of halal tourism in Indonesia.